Social bodies and social justice. Issue 3 (September 2019) - Lewis, Sam; Thomson, Michael
Abstract: This paper identifies and engages with the social bodies emerging by virtue of the social turn in the life sciences and recent embodied approaches to social justice. Across these diverse domains, bodies are being narrated as shaped by and dependent on their environments. To explore this potentially important and productive convergence, we bring Martha Fineman's vulnerability theory into conversation with neuroscience and environmental epigenetics. We foreground significant intersecting concerns and argue that vulnerability theory – and other embodied models of social justice – is strengthened by taking embodiment seriously, including attending to the social turn in the life sciences. This can enhance the potential traction of these progressive theories. These in turn provide an alternative theoretical framework to the neoliberal lens through which neuroscience and epigenetics have hitherto been translated into policy and practice. We nevertheless acknowledge the potential limitations and dangers of the current biopolitical landscape.